Rozumieć codzienność – z punktu widzenia antropologii interpretatywnej Clifforda Geertza - Lubowicka, Grażyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The paper looks at the problem of understanding daily reality, which presents a challenge for the humanities, arts and social sciences today. The problem can be considered from two perspectives: first, as a problem relating to the method, interpretation, observation, study of daily reality; and second, as a problem or a question that every individual entangled in and belonging to daily reality can put to themselves, i.e. how to understand oneself in the context of one’s own daily reality? The answer to the question about possible access to daily reality is based on the assumption that that access requires understanding which is a complex mental operation performed by a researcher and susceptible of being performed by every individual. The paper discusses understanding of daily reality with reference to the ideas of contemporary cultural anthropologist Clifford Geertz. The cultural anthropology solutions Geertz proposed can both provide a methodological basis for conceptualising understanding of individuals or social groups under study, and prove useful in the individual’s reflection and deliberation on themselves.
Keywords: Clifford Geertz; culture; daily reality; interpretive anthropology; symbolic system; understanding